Was Was dalam Shalat Perspektif Psikologi - Ziadatulilmi Zainuddin Putri; Robingatun Robingatun; Nur Aziz Affandi; Novi Wahyu Winastuti (Gunung Djati Conference Series, 2023)
This study aims to discuss the problem of anxious from the perspective of religion and psychology, as well as how to overcome it. This study uses a qualitative approach by applying descriptive analytical methods. The results of this study indicate that anxious behavior or OCD occurs when there is a push from outside human control, which when it is not carried out will cause anxiety, although it cannot be completely cured, it turns out that anxious or OCD can be minimized in various ways.